UPAYA PASANGAN SUAMI ISTRI BEDA BUDAYA DALAM MEMBENTUK KELUARGA SAKINAH (STUDI KASUS PASANGAN SUAMI ISTRI BEDA BUDAYA DESA WAELO KECAMATAN WAELATA KABUPATEN BURU NAMLEA) - Lailiyatur Rohmah; Khoirul Asfiyak; Faridatus Sa’adah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
A different cultural wedding is a marriage that takes place between a couple who come from a different background. Differences in thought and way of life can lead to a conflict. So the researchers would like to describe the conflicts that developed and how different cultural couples were trying to from the perfect family. The studi uses a qualitative approach with a type of case study. Studies suggest that these cultural background differences resulted in conflict within the marriiage. So couples in different cultures make an effort to resolve these conflicts. The maariages they undergo ore due to an adjustment or adaptation to the environtment and community. And adjustments to the spouse also made.